Evaluating effectiveness of cross-culture mission strategies in the modern Christian church: navigating diversity, promoting peace, and connecting across cultures - Parks, Camree, author (Colorado State University. Libraries, 2024)
This thesis explores effective strategies for Christian missionary work, emphasizing the importance of relational, cross-cultural, and sustainable approaches. Drawing on a case study of Timberline Church's mission trip to Comolapa, Guatemala, the research demonstrates how prioritizing relationships over proselytizing fosters authentic connections and meaningful impact. The study is grounded in an interdisciplinary framework, integrating theological principles, cultural competence, and insights from community development literature. The findings highlight the value of transformational development, which encourages collaboration with local communities to address spiritual, social, and environmental needs. By engaging in activities such as building greenhouses, planting trees, and participating in local customs, the mission team demonstrated incarnational ministry—living and working alongside the community to embody the message of Christ through presence and service. This research contributes to contemporary discourse on missionary work by challenging traditional, evangelism-heavy models and advocating for a holistic approach that respects cultural diversity and promotes long-term sustainability. The insights gained from this study have significant implications for churches and mission organizations, suggesting a paradigm shift toward relational engagement and cultural sensitivity. Ultimately, this thesis underscores the transformative potential of missions that prioritize love, respect, and mutual growth.
Honors.
Keywords: missions; Christian; cross-culture